Preparation method and application of pre-coating transfer metal material

By pre-coating the thermoplastic resin layer, metal layer and adhesive layer on the deplastic film substrate, the problems of complex processes and environmental pollution of traditional packaging materials are solved, and environmentally friendly and efficient production of metal texture packaging materials are achieved.

CN119410281APending Publication Date: 2025-02-11TENGJIN (GUANGDONG) ENVIRONMENTAL PROTECTION MATERIALS TECHNOLOGY CO LTD
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202411301400.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-18
Publication Date
2025-02-11

AI Technical Summary

Technical Problem

The preparation process of traditional metal texture packaging materials is complex, has high cost, and has serious environmental pollution. The non-degradability of the materials leads to environmental problems such as white pollution.

Method used

Use a deplastic film as the substrate, and directly apply the thermoplastic resin layer, metal layer and adhesive layer on the substrate through a pre-coating process to simplify the production process, reduce costs, and improve environmental protection performance.

Benefits of technology

It realizes environmentally friendly, efficient and cost-effective metal texture packaging material production, enhances the adhesion and fold resistance of the material, and reduces environmental pollution.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005047770400000131
    Figure BDA0005047770400000131
  • Figure BDA0005047770400000141
    Figure BDA0005047770400000141
  • Figure BDA0005047770400000142
    Figure BDA0005047770400000142
Patent Text Reader

Abstract

The invention discloses a preparation method and application of a pre-coating transfer metal material, and belongs to the technical field of packaging materials, the method adopts a plastic removal film as a base material, and the base material is sequentially coated with a thermoplastic resin layer, a metal layer, a protective layer and an adhesive layer to form the pre-coating transfer metal material of a multi-layer structure. Compared with the prior art, the pre-coating transfer metal material has excellent metal texture and visual effect, has the characteristics of environmental protection and degradability, and is suitable for the high-end packaging fields of cigarette cases, cards, gift packaging and the like. According to the preparation method, the production process is simplified, the cost is reduced, the production efficiency is improved, secondary processing is not needed, transfer of metal color patterns can be achieved through direct hot pressing, and the requirements of the market for environment-friendly and high-performance packaging materials are met.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of packaging materials, and in particular to a preparation method of a pre-coated transfer metal material and application thereof. Background Art

[0002] In the modern packaging industry, metallic packaging materials are favored for their unique appearance and texture, especially in the packaging of high-end products such as cigarette boxes, cosmetic boxes and gift cards. However, traditional metallic packaging materials usually use plastic substrates and achieve metallic effects through complex process flows, which are not only costly but also impose a considerable burden on the environment. In addition, the non-degradability of plastic materials has led to increasingly serious environmental problems, such as white pollution.

[0003] The traditional method of preparing metallized packaging materials involves multiple steps, including the selection of substrates, the application of metal coatings, the printing of patterns and the final bonding. These steps often need to be carried out at different production stages, increasing logistics costs and production time. At the same time, the secondary processing of metal coatings may also lead to unstable material properties, affecting the quality of the final product.

[0004] In the prior art, Chinese invention patent CN106585144A discloses a cigarette box printing process, which is characterized by comprising the following steps: (1) cutting the printing substrate according to the packaging requirements of the packaged object; (2) applying pressure to the surface of the printing substrate cut in step (1) through a dot grating mold, so that a groove pattern is formed on the surface of the printing substrate; (3) transferring the silver paste mixture into the groove of the groove pattern pressed in step (2) by gravure printing; (4) hot stamping the groove of the printed semi-finished product surface in step (3) by using a hot stamping machine; (5) applying a curing resin on the surface of the printed substrate by screen printing after the printed semi-finished product is treated in step (4); (6) cutting the polyethylene heat shrink film according to the size of the printed substrate cut in step (1). The cigarette box printing process of the invention has high wear resistance at the silver-coated surface of the finished cigarette box, and the printed layer is smooth and delicate. However, the cigarette box printing process of the invention is not environmentally friendly, the processing technology is complicated, and the adhesion and folding resistance are poor. Summary of the invention

[0005] In view of these defects of the prior art, the present invention proposes a method for preparing a pre-coated transfer metal material, aiming to achieve the production of environmentally friendly, efficient and cost-effective metal texture packaging materials through an innovative process flow. The present invention uses a de-plasticized film as a substrate, and directly applies a thermoplastic resin layer, a metal layer and an adhesive layer on the substrate through a pre-coating process, thereby eliminating multiple processing and post-processing steps in the traditional process, thereby simplifying the production process, reducing production costs, and improving the environmental performance of the product, and enhancing the adhesion and folding resistance of the material.

[0006] In order to achieve the above-mentioned object of the invention, the present invention adopts the following technical solutions:

[0007] A method for preparing a pre-coated transfer metal material is as follows:

[0008] Step 1: Prepare the substrate: Select the plastic film as the substrate. The substrate is made of BOPP material and the thickness of the substrate is 12-18 μm.

[0009] Step 2, thermoplastic resin layer: directly coating the thermoplastic resin on the plastic film substrate; placing the coated substrate in a dry environment, setting the drying temperature at 40-80°C, the drying time is 1 hour, forming the desired pattern on the thermoplastic resin layer by a molding process, and before molding, preheating the material at 150-170°C for 20-40 minutes, setting the molding temperature at 120-200°C, applying the molding pressure at 18-22MPa, holding the pressure for 3-5 minutes, and the coating thickness is 4-6μm;

[0010] Step 3, metal layer: adding a metal layer on the thermoplastic resin layer by vacuum plating;

[0011] Step 4, adhesive layer: apply hot melt adhesive on the protective layer at 160-180°C. The working time of the hot melt adhesive is about 10-20 seconds, the curing speed is 8-12 seconds, and the thickness is 8-12 μm.

[0012] Preferably, the preparation method of the pre-coated transfer metal material is as follows:

[0013] Step 1: Prepare the substrate: Select the plastic film as the substrate. The substrate is made of BOPP material and the thickness of the substrate is 12-18 μm.

[0014] Step 2, thermoplastic resin layer: directly coating the thermoplastic resin on the plastic film substrate; placing the coated substrate in a dry environment, setting the drying temperature at 40-80°C, the drying time is 1 hour, forming the desired pattern on the thermoplastic resin layer by a molding process, and before molding, preheating the material at 150-170°C for 20-40 minutes, setting the molding temperature at 120-200°C, applying the molding pressure at 18-22MPa, holding the pressure for 3-5 minutes, and the coating thickness is 4-6μm;

[0015] Step 3, metal layer: adding a metal layer on the thermoplastic resin layer by vacuum plating;

[0016] Step 4, protective layer: spray a protective layer on the metal layer;

[0017] Step 5, adhesive layer: apply hot melt adhesive on the protective layer at 160-180°C. The working time of the hot melt adhesive is about 10-20 seconds, the curing speed is 8-12 seconds, and the thickness is 8-12 μm.

[0018] The thermoplastic resin is at least one of polyethylene, polypropylene and polyester.

[0019] The metal layer may be at least one of gold, silver, copper, and alloy metal materials.

[0020] The vacuum degree of the vacuum plating in step 3 is 1×10 -2 ~1×10 -3 Pa, time 1 to 3 minutes, thickness 2 to 4 μm.

[0021] The protective layer in step 4 is made of polyurethane material; the spraying pressure in step 4 is 0.5-1 MPa, and after spraying, it is dried at 40-80° C. for 2-8 hours, and the thickness is 4-6 μm.

[0022] The hot melt adhesive is one of EVA hot melt adhesive and modified hot melt adhesive.

[0023] The preparation method of the modified hot melt adhesive is as follows, in parts by weight:

[0024] S1, mixing 20 to 25 parts of cyclohexane oil, 4 to 8 parts of 4-fluoro-4'-hydroxybenzophenone, 12 to 18 parts of styrene-ethylene-butylene-styrene block copolymer and 0.5 to 2 parts of butylated hydroxyanisole; heating at 170 to 190° C. for 1 to 3 hours to obtain a pretreated product;

[0025] S2, 1 to 3 parts of aluminum-titanium composite coupling agent JTW-1618 and 2 to 4 parts of isopropanolamine are mixed and stirred for 5 to 15 minutes, then 0.5 to 2 parts of hydroxypropyl distarch phosphate are added, and stirring is continued for 10 to 30 minutes to obtain an enhancer;

[0026] S3, preheat the reaction container to 130-150°C, and add 8-12 parts of cycloparaffin oil and 5-10 parts of isoprene rubber; heat to 160-180°C and stir until uniformly mixed; then, add the pretreated material prepared in step S1, and continue stirring until completely fused; under stirring, add 3-5 parts of the reinforcing agent prepared in step S2 and 5-10 parts of C5C9 copolymer petroleum resin, and after they are melted, add 5-10 parts of terpene resin; during the whole process, maintain the temperature at 160-180°C and stir under a nitrogen environment to ensure uniform mixing of the materials. Finally, perform vacuum treatment and continue stirring until a uniform modified hot melt adhesive is obtained.

[0027] The pre-coated transfer metal material is applied to cigarette boxes, cosmetic boxes, and gift cards.

[0028] In the method for preparing the pre-coated transfer metal material of the present invention, the functions of each step are as follows:

[0029] The substrate preparation is to choose plastic-free film as the substrate. This material is environmentally friendly and degradable, does not contain plastic raw materials, and has good environmental characteristics. The substrate is made of BOPP material, has a matte effect and recyclability, and has a thickness of 12 to 18μm, providing a solid foundation for subsequent coating.

[0030] The thermoplastic resin layer is formed by directly coating the thermoplastic resin on the substrate. The desired pattern is formed on the resin layer through drying and molding processes. This step ensures the accuracy of the pattern and the uniformity of the resin layer, providing a good surface for the attachment of the metal layer.

[0031] The metal layer is added on the thermoplastic resin layer by vacuum plating technology, such as gold, silver, copper or alloy. Vacuum plating is carried out in a high vacuum environment to ensure the uniformity and adhesion of the metal layer. At the same time, the metal layer gives the product a special metal effect and decorativeness.

[0032] The protective layer is a polyurethane material sprayed on the metal layer as a protective layer to enhance the product's folding and scratch resistance and allow subsequent printing or other processing. The thickness and drying time of the protective layer are adjusted according to the material characteristics and product requirements.

[0033] The adhesive layer is a powdered adhesive material coated on the protective layer, usually using hot melt adhesive. Hot melt adhesive melts and is applied at a specific temperature, solidifies quickly, and forms a stable adhesive layer. This step ensures that the pre-coated transfer metal material can adhere firmly to the target substrate, such as white cardboard or other paper.

[0034] In the preparation method of the modified hot melt adhesive, the functions of each substance are as follows:

[0035] Naphthenic oil helps to reduce the melt viscosity of hot melt adhesive, improve its fluidity and coating properties, and also helps to improve the flexibility and bonding properties of hot melt adhesive.

[0036] 4-Fluoro-4'-hydroxybenzophenone improves the thermal stability and light stability of the hot melt adhesive and may also participate in the cross-linking reaction to enhance the cohesive force of the hot melt adhesive.

[0037] Styrene-ethylene-butylene-styrene block copolymer provides the basic physical properties of hot melt adhesive, such as elasticity, adhesion, aging resistance, etc. Its block structure makes the hot melt adhesive have good compatibility and mechanical properties.

[0038] Butylated hydroxyanisole prevents hot melt adhesive from thermal or light degradation during processing and use, extending its service life.

[0039] Aluminum-titanium composite coupling agent JTW-1618 is used as a coupling agent, which can enhance the compatibility between inorganic fillers and organic resins and improve the bonding strength and heat resistance of hot melt adhesives.

[0040] Isopropanolamine helps mix and disperse coupling agents and other additives, and may also participate in certain chemical reactions to improve the performance of hot melt adhesives.

[0041] Hydroxypropyl distarch phosphate may be used as a thickener or stabilizer to increase the viscosity of hot melt adhesives and improve their bonding properties and anti-sagging properties.

[0042] As a rubber component, isoprene rubber provides elasticity and flexibility to the hot melt adhesive and improves its low temperature performance and impact resistance.

[0043] C5C9 copolymer petroleum resin improves the bonding strength and heat resistance of hot melt adhesives and enhances their bonding ability to a variety of substrates.

[0044] Terpene resins provide the bonding, aging and chemical resistance of hot melt adhesives while improving their environmental friendliness.

[0045] The purpose of the entire preparation method is to manufacture a pre-coated transfer material with a metallic effect, which can be conveniently applied to various packaging materials, such as cigarette boxes, cards, etc., to provide an environmentally friendly, efficient and economical metallic effect packaging solution.

[0046] Compared with the prior art, it has the following beneficial effects:

[0047] 1) The plastic-free film substrate used in the present invention is an environmentally friendly material, does not contain plastic raw materials, and is degradable, which meets the current global requirements for environmental protection and sustainable development. Compared with traditional plastic substrates, the plastic-free film reduces pollution to the environment, especially in the field of packaging materials, which is particularly important.

[0048] 2) The present invention uses a pre-coating process, and the metal layer and the adhesive layer are directly coated on the substrate during the production process, thereby achieving online bonding and eliminating the traditional secondary processing steps. This not only improves production efficiency, but also reduces production costs, making the product more competitive in the market.

[0049] 3) The present invention adds a polyurethane protective layer on the metal layer, which improves the folding and scratch resistance of the product, making the final product more durable. At the same time, the use of modified hot melt adhesive provides better adhesion and folding resistance, which makes the pre-coated transfer metal material show higher durability and reliability in practical applications, especially in the field of high-end packaging. These characteristics are crucial to ensure the beauty and functionality of the product.

[0050] 4) The pre-coated transfer metal material of the present invention can be widely used in packaging that requires a metal effect, such as cigarette boxes, cards, etc., providing a novel metal effect packaging solution. The innovative application of this material broadens the selection range of packaging materials and meets the market demand for diversified and personalized packaging. DETAILED DESCRIPTION

[0051] Polyethylene, Jiangyin Ximalun Environmental Protection Technology Co., Ltd., high density, product specifications: 300 mesh, brand: HP18.

[0052] Tetrapropyl zirconate, Hubei Langbowan Biotechnology Co., Ltd., single product number: lbw55668.

[0053] EVA hot melt adhesive, Dongguan Sanhong Adhesive Materials Co., Ltd., model: HS-5183.

[0054] The polyurethane material was purchased from Shunde New Materials (Shanghai) Co., Ltd., model number SWD9594.

[0055] Naphthenic oil, Dezhou Mingsheng Chemical Co., Ltd., model: 4006.

[0056] Styrene-ethylene-butylene-styrene block copolymer, Shanghai Aoji Chemical Co., Ltd., model: 353432.

[0057] Aluminate coupling agent JTW-181, titanate coupling agent JTW-101, and aluminum-titanium composite coupling agent JTW-1618 were all purchased from Nanjing Jingtianwei Chemical Co., Ltd.

[0058] Isoprene rubber, Shanghai Yuanxiang Industrial Co., Ltd., brand: SKI-3S.

[0059] Terpene resin was purchased from Kraton Chemicals, USA, model TRA25L.

[0060] Phenolic resin, Shenzhen Jitian Chemical Co., Ltd., model: BF01.

[0061] Rosin resin, Shanghai Sanlian Industrial Co., Ltd., brand: RE-100L.

[0062] C5C9 copolymer petroleum resin, Shanghai Baitai New Materials Co., Ltd., model: HH2-1004.

[0063] Polyamide hot melt adhesive, Foshan Junyi Rubber & Plastic Technology Co., Ltd., item number: BU-160.

[0064] PES hot melt adhesive, Zhejiang Aoyu New Material Technology Co., Ltd., model: AY8501.

[0065] Polyolefin hot melt adhesive, Wuhan Tengxiang Industrial Technology Co., Ltd., model: supra181.

[0066] The remaining raw materials in the examples and comparative examples of the present invention are all commercially available products.

[0067] The design idea of ​​the present invention is to innovate a method for preparing a pre-coated transfer metal material, aiming to provide an environmentally friendly, efficient and metal-effect packaging material. By using a plastic-free film as a substrate, and sequentially constructing a thermoplastic resin layer, a metal layer, a protective layer and an adhesive layer thereon, a multi-layer structure of a pre-coated transfer metal material is formed. The method ensures the quality and performance of the product by precisely controlling the coating, drying, curing and electroplating process parameters of each layer. In particular, in the preparation of the thermoplastic resin layer, a specific preheating, molding and drying process is adopted, and in the preparation of the metal layer, a high vacuum electroplating technology is adopted to ensure the uniformity and adhesion of the metal layer. The introduction of the protective layer enhances the folding and scratch resistance of the product, while the carefully selected adhesive layer material ensures the bonding strength and application adaptability of the final product. In addition, the present invention also specially designs a method for preparing a modified hot melt adhesive to improve the performance of the adhesive layer, making it more suitable for specific application requirements, such as high-end packaging fields such as cigarette boxes and cards. Overall, the present invention not only optimizes the traditional process and reduces production costs, but also improves production efficiency and product quality, meeting the market demand for environmentally friendly and high-performance packaging materials.

[0068] Example 1

[0069] A method for preparing a pre-coated transfer metal material is as follows:

[0070] Step 1: Prepare the substrate: Select the plastic film as the substrate. The substrate is made of BOPP material and the thickness is 15μm.

[0071] Step 2, thermoplastic resin layer: polyethylene is directly coated on the de-molding film substrate; the coated substrate is placed in a dry environment, the drying temperature is set at 50°C, the drying time is 1 hour, and the desired pattern is formed on the thermoplastic resin layer by a molding process. Before molding, the material is preheated at 160°C for 30 minutes, the molding temperature is set at 180°C, the molding pressure is applied at 20MPa, the holding time is maintained for 4 minutes, and the coating thickness is 5μm;

[0072] Step 3: Metal layer: Add a layer of silver on the thermoplastic resin layer by vacuum plating with a vacuum degree of 5×10 -3 Pa, time 2 minutes, thickness 3 μm;

[0073] Step 4, adhesive layer: apply EVA hot melt adhesive on the metal layer at 170°C. The working time of the hot melt adhesive is 15 seconds, the curing speed is 10 seconds, and the thickness is 10 μm.

[0074] Example 2

[0075] A method for preparing a pre-coated transfer metal material is as follows:

[0076] Step 1. Substrate preparation: Select plastic film as the substrate, the substrate is made of BOPP material, and the thickness of the substrate is 15μm;

[0077] Step 2, thermoplastic resin layer: polyethylene is directly coated on the de-molding film substrate; the coated substrate is placed in a dry environment, the drying temperature is set at 50°C, the drying time is 1 hour, and the desired pattern is formed on the thermoplastic resin layer by a molding process. Before molding, the material is preheated at 160°C for 30 minutes, the molding temperature is set at 180°C, the molding pressure is applied at 20MPa, the holding time is maintained for 4 minutes, and the coating thickness is 5μm;

[0078] Step 3: Metal layer: Add a layer of silver on the thermoplastic resin layer by vacuum plating with a vacuum degree of 5×10 -3 Pa, time 2 minutes, thickness 3 μm;

[0079] Step 4, protective layer: spray a protective layer on the metal layer using polyurethane material, the spraying pressure is 0.8MPa, dry at 60℃ for 4 hours, and the thickness is 5μm;

[0080] Step 5, adhesive layer: apply EVA hot melt adhesive on the protective layer at 170°C. The working time of the hot melt adhesive is 15 seconds, the curing speed is 10 seconds, and the thickness is 10 μm.

[0081] Example 3

[0082] A method for preparing a pre-coated transfer metal material is as follows:

[0083] Step 1: Prepare the substrate: Select the plastic film as the substrate. The substrate is made of BOPP material and the thickness is 15μm.

[0084] Step 2, thermoplastic resin layer: polyethylene is directly coated on the de-molding film substrate; the coated substrate is placed in a dry environment, the drying temperature is set at 50°C, the drying time is 1 hour, and the desired pattern is formed on the thermoplastic resin layer by a molding process. Before molding, the material is preheated at 160°C for 30 minutes, the molding temperature is set at 180°C, the molding pressure is applied at 20MPa, the holding time is maintained for 4 minutes, and the coating thickness is 5μm;

[0085] Step 3: Metal layer: Add a layer of silver on the thermoplastic resin layer by vacuum plating with a vacuum degree of 5×10 -3 Pa, time 2 minutes, thickness 3 μm;

[0086] Step 4, protective layer: spray a protective layer on the metal layer using polyurethane material, the spraying pressure is 0.8MPa, dry at 60℃ for 4 hours, and the thickness is 5μm;

[0087] Step 5, adhesive layer: apply hot melt adhesive on the protective layer. The hot melt adhesive is a modified hot melt adhesive. The coating is performed at 170°C. The working time of the hot melt adhesive is 15 seconds, the curing speed is 10 seconds, and the thickness is 10μm.

[0088] The preparation method of the modified hot melt adhesive is as follows:

[0089] S1, 23 kg of cyclohexane oil, 6 kg of 4-fluoro-4'-hydroxybenzophenone, 15 kg of styrene-ethylene-butylene-styrene block copolymer and 1 kg of butylated hydroxyanisole were mixed; heated at 180° C. for 2 hours to obtain a pretreated product;

[0090] S2, 2 kg of aluminum-titanium composite coupling agent JTW-1618 and 3 kg of isopropanolamine were mixed and stirred for 10 min, and then 1 kg of hydroxypropyl distarch phosphate was added, and stirring was continued for 20 min to obtain a reinforcing agent;

[0091] S3, preheat the reaction container to 140 ° C, and add 10 kg of cyclohexane oil and 8 kg of isoprene rubber; heat to 170 ° C and stir until uniformly mixed; then, add the pretreated material prepared in step S1, and continue stirring until completely fused; under stirring, add 4 kg of the reinforcing agent prepared in step S2 and 8 kg of C5C9 copolymer petroleum resin, and after they are melted, add 8 kg of terpene resin; during the whole process, maintain the temperature at 170 ° C and stir under a nitrogen environment to ensure uniform mixing of the materials. Finally, perform vacuum treatment and continue stirring until a uniform modified hot melt adhesive is obtained.

[0092] Example 4

[0093] The preparation method of a pre-coated transfer metal material is basically the same as that of Example 3, the only difference being that the preparation method of the modified hot melt adhesive is different.

[0094] The preparation method of the modified hot melt adhesive is as follows:

[0095] S1, 23 kg of cyclohexane oil, 6 kg of 4-fluoro-4'-hydroxybenzophenone, 15 kg of styrene-ethylene-butylene-styrene block copolymer and 1 kg of butylated hydroxyanisole were mixed; heated at 180° C. for 2 hours to obtain a pretreated product;

[0096] S2, 2 kg of tetra-n-propyl zirconate and 3 kg of isopropanolamine were mixed and stirred for 10 min, and then 1 kg of hydroxypropyl distarch phosphate was added, and stirring was continued for 20 min to obtain an enhancer;

[0097] S3, preheat the reaction container to 140 ° C, and add 10 kg of cyclohexane oil and 8 kg of isoprene rubber; heat to 170 ° C and stir until uniformly mixed; then, add the pretreated material prepared in step S1, and continue stirring until completely fused; under stirring, add 4 kg of the reinforcing agent prepared in step S2 and 8 kg of C5C9 copolymer petroleum resin, and after they are melted, add 8 kg of terpene resin; during the whole process, maintain the temperature at 170 ° C and stir under a nitrogen environment to ensure uniform mixing of the materials. Finally, perform vacuum treatment and continue stirring until a uniform modified hot melt adhesive is obtained.

[0098] Example 5

[0099] The preparation method of a pre-coated transfer metal material is basically the same as that of Example 3, the only difference being that the preparation method of the modified hot melt adhesive is different.

[0100] The preparation method of the modified hot melt adhesive is as follows:

[0101] S1, 23 kg of cyclohexane oil, 6 kg of 4-fluoro-4'-hydroxybenzophenone, 15 kg of styrene-ethylene-butylene-styrene block copolymer and 1 kg of butylated hydroxyanisole were mixed; heated at 180° C. for 2 hours to obtain a pretreated product;

[0102] S2, 2 kg of aluminate coupling agent JTW-181 and 3 kg of isopropanolamine were mixed and stirred for 10 min, then 1 kg of hydroxypropyl distarch phosphate was added, and stirring was continued for 20 min to obtain a reinforcing agent;

[0103] S3, preheat the reaction container to 140 ° C, and add 10 kg of cyclohexane oil and 8 kg of isoprene rubber; heat to 170 ° C and stir until uniformly mixed; then, add the pretreated material prepared in step S1, and continue stirring until completely fused; under stirring, add 4 kg of the reinforcing agent prepared in step S2 and 8 kg of C5C9 copolymer petroleum resin, and after they are melted, add 8 kg of terpene resin; during the whole process, maintain the temperature at 170 ° C and stir under a nitrogen environment to ensure uniform mixing of the materials. Finally, perform vacuum treatment and continue stirring until a uniform modified hot melt adhesive is obtained.

[0104] Example 6

[0105] The preparation method of a pre-coated transfer metal material is basically the same as that of Example 3, the only difference being that the preparation method of the modified hot melt adhesive is different.

[0106] The preparation method of the modified hot melt adhesive is as follows:

[0107] S1, 23 kg of cyclohexane oil, 6 kg of 4-fluoro-4'-hydroxybenzophenone, 15 kg of styrene-ethylene-butylene-styrene block copolymer and 1 kg of butylated hydroxyanisole were mixed; heated at 180° C. for 2 hours to obtain a pretreated product;

[0108] S2, 2 kg of titanate coupling agent JTW-101 and 3 kg of isopropanolamine were mixed and stirred for 10 min, then 1 kg of hydroxypropyl distarch phosphate was added, and stirring was continued for 20 min to obtain a reinforcing agent;

[0109] S3, preheat the reaction container to 140 ° C, and add 10 kg of cyclohexane oil and 8 kg of isoprene rubber; heat to 170 ° C and stir until uniformly mixed; then, add the pretreated material prepared in step S1, and continue stirring until completely fused; under stirring, add 4 kg of the reinforcing agent prepared in step S2 and 8 kg of C5C9 copolymer petroleum resin, and after they are melted, add 8 kg of terpene resin; during the whole process, maintain the temperature at 170 ° C and stir under a nitrogen environment to ensure uniform mixing of the materials. Finally, perform vacuum treatment and continue stirring until a uniform modified hot melt adhesive is obtained.

[0110] Example 7

[0111] The preparation method of a pre-coated transfer metal material is basically the same as that of Example 3, the only difference being that the preparation method of the modified hot melt adhesive is different.

[0112] The preparation method of the modified hot melt adhesive is as follows:

[0113] S1, 23 kg of cyclohexane oil, 6 kg of 4-fluoro-4'-hydroxybenzophenone, 15 kg of styrene-ethylene-butylene-styrene block copolymer and 1 kg of butylated hydroxyanisole were mixed; heated at 180° C. for 2 hours to obtain a pretreated product;

[0114] S2, 2 kg of aluminum-titanium composite coupling agent JTW-1618 and 3 kg of isopropanolamine were mixed and stirred for 10 min, and then 1 kg of hydroxypropyl distarch phosphate was added, and stirring was continued for 20 min to obtain a reinforcing agent;

[0115] S3, preheat the reaction container to 140 ° C, and add 10 kg of cyclohexane oil and 8 kg of isoprene rubber; heat to 170 ° C and stir until uniformly mixed; then, add the pretreated material prepared in step S1, and continue stirring until completely fused; under stirring, add 4 kg of the reinforcing agent prepared in step S2 and 8 kg of C5C9 copolymer petroleum resin, and after they are melted, add 8 kg of phenolic resin; during the whole process, maintain the temperature at 170 ° C and stir under a nitrogen environment to ensure uniform mixing of the materials. Finally, perform vacuum treatment and continue stirring until a uniform modified hot melt adhesive is obtained.

[0116] Example 8

[0117] The preparation method of a pre-coated transfer metal material is basically the same as that of Example 3, the only difference being that the preparation method of the modified hot melt adhesive is different.

[0118] The preparation method of the modified hot melt adhesive is as follows:

[0119] S1, 23 kg of cyclohexane oil, 6 kg of 4-fluoro-4'-hydroxybenzophenone, 15 kg of styrene-ethylene-butylene-styrene block copolymer and 1 kg of butylated hydroxyanisole were mixed; heated at 180° C. for 2 hours to obtain a pretreated product;

[0120] S2, 2 kg of aluminum-titanium composite coupling agent JTW-1618 and 3 kg of isopropanolamine were mixed and stirred for 10 min, and then 1 kg of hydroxypropyl distarch phosphate was added, and stirring was continued for 20 min to obtain a reinforcing agent;

[0121] S3, preheat the reaction container to 140 ° C, and add 10 kg of cyclohexane oil and 8 kg of isoprene rubber; heat to 170 ° C and stir until uniformly mixed; then, add the pretreated material prepared in step S1, and continue stirring until completely fused; under stirring, add 4 kg of the reinforcing agent prepared in step S2 and 8 kg of C5C9 copolymer petroleum resin, and after they are melted, add 8 kg of rosin resin; during the whole process, maintain the temperature at 170 ° C and stir under a nitrogen environment to ensure uniform mixing of the materials. Finally, perform vacuum treatment and continue stirring until a uniform modified hot melt adhesive is obtained.

[0122] Comparative Example 1

[0123] The preparation method of a pre-coated transfer metal material is basically the same as that of Example 3, the only difference being that the modified hot melt adhesive is different.

[0124] Replace modified hot melt adhesive with polyamide hot melt adhesive.

[0125] Comparative Example 2

[0126] The preparation method of a pre-coated transfer metal material is basically the same as that of Example 3, the only difference being that the modified hot melt adhesive is different.

[0127] Replace modified hot melt adhesive with PES hot melt adhesive.

[0128] Comparative Example 3

[0129] The preparation method of a pre-coated transfer metal material is basically the same as that of Example 3, the only difference being that the modified hot melt adhesive is different.

[0130] Replace modified hot melt adhesive with polyolefin hot melt adhesive.

[0131] Test Example 1

[0132] Adhesion performance test

[0133] When evaluating adhesion performance, first firmly fix the 3M600 type self-adhesive tape on the sample surface (make sure the length of the tape is not less than 25 mm, and it can be adjusted appropriately depending on the sample size). Next, use an eraser or hand to rub the tape repeatedly to ensure that the tape is in full contact with the test surface and to expel any air bubbles that may exist. Then, quickly pull up the tape at an angle of about 60 degrees (the pulling speed is controlled between 0.5 and 1 second) to complete a test. The adhesion performance can be evaluated by observing the degree of shedding of the pre-coated transfer metal material after the tape is peeled off. The strength of the adhesion performance is quantified according to the proportion of the shedding area.

[0134] The test results are shown in Table 1.

[0135] Table 1

[0136]

[0137]

[0138] Test Example 2

[0139] Folding performance test

[0140] In order to evaluate the folding resistance of the prepared pre-coated transfer metal material, the MIT folding resistance test equipment model HK-205T provided by Shanghai Xiangfan Instrument Co., Ltd. was used. During the test, the pre-coated transfer metal material was placed in a constant tensile force environment, and the force was set to 10N. Subsequently, the material was folded in both directions at a frequency of 175 cycles per minute, and the angle of each fold reached 135 degrees until the material broke in the folded area, and the number of folds when the break occurred was counted. Through this test method, the durability and reliability of the material under repeated folding can be quantified.

[0141] The test results are shown in Table 2.

[0142] Table 2

[0143]

[0144]

[0145] It can be seen from test examples 1 to 2 that the pre-coated transfer metal material obtained in Example 3 of the present invention has the best adhesion performance and folding resistance.

[0146] In Example 2, by adding a polyurethane material as a protective layer on the metal layer, the adhesion performance and folding resistance of the pre-coated transfer metal material are significantly improved compared to Example 1 without using the protective layer. The high elasticity and adhesion of polyurethane ensure its close bonding with the metal layer. At the same time, its excellent water resistance, corrosion resistance and rapid curing characteristics provide additional physical protection and chemical stability for the material, effectively preventing the adverse effects of environmental factors on the bonding performance. In addition, the anti-cracking effect of polyurethane further enhances the durability of the material under repeated folding or mechanical stress, thereby showing more excellent folding resistance in practical applications.

[0147] The modified hot melt adhesive used in Example 3 of the present invention exhibits better adhesion and folding resistance than the hot melt adhesives in other embodiments and comparative examples. This result may be attributed to the unique formula and preparation method of the modified hot melt adhesive. Ingredients such as cyclohexane oil, 4-fluoro-4'-hydroxybenzophenone, styrene-ethylene-butylene-styrene block copolymer and butylated hydroxyanisole are used in the modified hot melt adhesive, which are pretreated by heating at 180°C for 2 hours to form a pretreated material with good bonding properties. Subsequently, the bonding strength and cohesion of the hot melt adhesive are further improved by adding an enhancer prepared by adding aluminum-titanium composite coupling agent JTW-1618, isopropanolamine and hydroxypropyl distarch phosphate. In the final preparation process of the modified hot melt adhesive, the uniform mixing of the materials is ensured by continuous stirring and vacuum treatment under a nitrogen environment, thereby obtaining a hot melt adhesive product with uniform performance. This modified hot melt adhesive can form a stronger bonding effect during the bonding process, which may be due to the special ingredients and preparation process in its formula, which enables the hot melt adhesive to better wet and penetrate into the surface of the metal layer during the cooling and solidification process, forming more bonding points, thereby improving the adhesion performance. In addition, the folding resistance of the modified hot melt adhesive may benefit from its unique molecular structure and compatibility, which enables the hot melt adhesive to better absorb and disperse stress during repeated folding, reduce the generation and expansion of cracks, and thus improve the folding resistance of the pre-coated transfer metal material. In contrast, EVA hot melt adhesive, polyamide hot melt adhesive, PES hot melt adhesive and polyolefin hot melt adhesive may have certain limitations in formula design, bonding principle, substrate treatment, etc., resulting in their inferior adhesion and folding resistance to modified hot melt adhesives. These hot melt adhesives may differ from modified hot melt adhesives in terms of compatibility between tackifying resin and base resin, molecular weight distribution, polar group content, etc., thus affecting their final application performance.

[0148] In Example 3, the aluminum-titanium composite coupling agent JTW-1618 exhibits better adhesion and folding resistance than the tetra-n-propyl zirconate of Example 4, the aluminate coupling agent JTW-181 of Example 5, and the titanate coupling agent JTW-101 of Example 6. This may be due to the unique properties and mechanism of action of the aluminum-titanium composite coupling agent JTW-1618. The aluminum-titanium composite coupling agent JTW-1618 is a highly efficient surface treatment agent that can significantly improve the compatibility and adhesion between metal materials and organic polymers. It improves the interfacial bonding between the metal material and the resin by forming a chemically bonded organic layer on the surface of the metal material. The molecular structure of this coupling agent contains aluminum and titanium elements, which may give it higher reactivity and better wettability, thereby improving the adhesion and folding resistance of the material. In contrast, although tetra-n-propyl zirconate is also an organic metal compound, commonly used in organic synthesis, catalysts and surface treatment, it may not be as effective as aluminum-titanium composite coupling agent JTW-1618 in improving adhesion and folding resistance. Although aluminate coupling agent JTW-181 and titanate coupling agent JTW-101 are also used to improve the compatibility between polymers and metal materials, they may not be as good as aluminum-titanium composite coupling agent JTW-1618 in some properties.

[0149] In Example 3, terpene resin is used as a component of the modified hot melt adhesive, which shows better adhesion and folding resistance than the phenolic resin and rosin resin used in other embodiments. Terpene resin is a resin processed from natural turpentine oil, which has good properties such as transparency, non-toxicity, neutrality, electrical insulation, hydrophobicity, non-crystallization, resistance to dilute acid and alkali, heat resistance, light resistance, anti-aging and strong adhesion, and has good compatibility with various synthetic substances. These characteristics make the application of terpene resin in adhesives outstanding, especially in hot melt adhesives, where it can provide good bonding strength and temperature resistance. In contrast, although phenolic resin is also an important adhesive resin with good adhesive properties, its water resistance and aging resistance may not be as good as terpene resin. In addition, the stability of phenolic resin at high temperature may not be as good as terpene resin, which may affect its application effect in pre-coated transfer metal materials. Rosin resin is a widely used adhesive resin, but it is easily oxidized and isomerized, and usually needs to be modified to improve its performance. Although the modified rosin has improved some properties, it may still be inferior to terpene resin in terms of adhesion and folding resistance.

Claims

1. A method for preparing a pre-coated transfer metal material, characterized in that: Here’s how: Step 1: Prepare the substrate: Select the plastic film as the substrate. The substrate is made of BOPP material and the thickness of the substrate is 12-18 μm. Step 2, thermoplastic resin layer: directly coating the thermoplastic resin on the plastic film substrate; placing the coated substrate in a dry environment, setting the drying temperature at 40-80°C, the drying time is 1 hour, forming the desired pattern on the thermoplastic resin layer by a molding process, and before molding, preheating the material at 150-170°C for 20-40 minutes, setting the molding temperature at 120-200°C, applying the molding pressure at 18-22MPa, holding the pressure for 3-5 minutes, and the coating thickness is 4-6μm; Step 3, metal layer: adding a metal layer on the thermoplastic resin layer by vacuum plating; Step 4, adhesive layer: apply hot melt adhesive on the protective layer at 160-180°C. The working time of the hot melt adhesive is about 10-20 seconds, the curing speed is 8-12 seconds, and the thickness is 8-12 μm.

2. The method for preparing the pre-coating transfer metal material according to claim 1, characterized in that: Here’s how: Step 1: Prepare the substrate: Select the plastic film as the substrate. The substrate is made of BOPP material and the thickness of the substrate is 12-18 μm. Step 2, thermoplastic resin layer: directly coating the thermoplastic resin on the plastic film substrate; placing the coated substrate in a dry environment, setting the drying temperature at 40-80°C, the drying time is 1 hour, forming the desired pattern on the thermoplastic resin layer by a molding process, and before molding, preheating the material at 150-170°C for 20-40 minutes, setting the molding temperature at 120-200°C, applying the molding pressure at 18-22MPa, holding the pressure for 3-5 minutes, and the coating thickness is 4-6μm; Step 3, metal layer: adding a metal layer on the thermoplastic resin layer by vacuum plating; Step 4, protective layer: spray a protective layer on the metal layer; Step 5, adhesive layer: apply hot melt adhesive on the protective layer at 160-180°C. The working time of the hot melt adhesive is about 10-20 seconds, the curing speed is 8-12 seconds, and the thickness is 8-12 μm.

3. The method for preparing the pre-coated transfer metal material according to claim 1 or 2, characterized in that: The thermoplastic resin is at least one of polyethylene, polypropylene and polyester.

4. The method for preparing the pre-coated transfer metal material according to claim 1 or 2, characterized in that: The metal layer may be at least one of gold, silver, copper, and alloy metal materials.

5. The method for preparing the pre-coating transfer metal material according to claim 1 or 2, characterized in that: The vacuum degree of the vacuum plating in step 3 is 1×10 -2 ~1×10 -3 Pa, time 1 to 3 minutes, thickness 2 to 4 μm.

6. The method for preparing the pre-coating transfer metal material according to claim 2, characterized in that: The protective layer in step 4 is made of polyurethane material; the spraying pressure in step 4 is 0.5-1 MPa, and after spraying, it is dried at 40-80° C. for 2-8 hours, and the thickness is 4-6 μm.

7. The method for preparing the pre-coating transfer metal material according to claim 1 or 2, characterized in that: The hot melt adhesive is one of EVA hot melt adhesive and modified hot melt adhesive.

8. The method for preparing the pre-coating transfer metal material according to claim 7, characterized in that: The preparation method of the modified hot melt adhesive is as follows, in parts by weight: S1, mixing 20 to 25 parts of cyclohexane oil, 4 to 8 parts of 4-fluoro-4'-hydroxybenzophenone, 12 to 18 parts of styrene-ethylene-butylene-styrene block copolymer and 0.5 to 2 parts of butylated hydroxyanisole; heating at 170 to 190° C. for 1 to 3 hours to obtain a pretreated product; S2, 1 to 3 parts of aluminum-titanium composite coupling agent JTW-1618 and 2 to 4 parts of isopropanolamine are mixed and stirred for 5 to 15 minutes, then 0.5 to 2 parts of hydroxypropyl distarch phosphate are added, and stirring is continued for 10 to 30 minutes to obtain an enhancer; S3, preheat the reaction container to 130-150°C, and add 8-12 parts of cycloparaffin oil and 5-10 parts of isoprene rubber; heat to 160-180°C and stir until uniformly mixed; then, add the pretreated material prepared in step S1, and continue stirring until completely fused; under stirring, add 3-5 parts of the reinforcing agent prepared in step S2 and 5-10 parts of C5C9 copolymer petroleum resin, and after they are melted, add 5-10 parts of terpene resin; during the whole process, maintain the temperature at 160-180°C and stir under a nitrogen environment to ensure uniform mixing of the materials. Finally, perform vacuum treatment and continue stirring until a uniform modified hot melt adhesive is obtained.

9. A pre-coated transfer metal material, characterized in that: The preparation method is as described in any one of claims 1 to 8.

10. An application of the pre-coated transfer metal material as claimed in claim 9, characterized in that: Applied to cigarette boxes, cosmetic boxes, gift cards.

Citation Information

Patent Citations

  • Print technology for cigarette cases

    CN106585144A